Organização Social do Cuidado em contexto de envelhecimento populacional sob o olhar de perspectivas teóricas e práticas - Fallaci, Isabella Vittoria (Universidade Federal de São Carlos, 2026)
Care work carries a historical burden of responsibility placed on families and, above all, on women; however, we have observed an increase in this burden with the rise of neoliberalism, the crisis in social protection systems and the erosion of labour rights, all of which are key socio-economic features of Latin America. From the perspective of care as work, a necessity and an inherent human activity, the work of caring for older people is mostly unpaid and takes place within a common context of nformality, with little social recognition, vulnerable coverage by social protection systems, and institutional and occupational precariousness. Objective: To explore and analyse the social organisation of unpaid care work, performed by women and directed towards older people, from theoretical and practical perspectives. Methodology: The research adopts a qualitative approach, with a descriptive-exploratory design carried out through semi-structured interviews. Two women participated in the study, meeting the following criteria: female gender; being an unpaid carer of an elderly person; being aged 18 or over; residing in the municipality of São Carlos, São Paulo; and having a per capita family income equal to or less than the minimum wage. The research was approved by the Research Ethics Committee (CEP). Results: Based on the analysis of the results, theoretically underpinned by Marxist feminist debates such as the Theory of Social Reproduction, care for older people, despite its specific characteristics, when unpaid, has been socially structured around overburdening, precariousness, invisibility and a lack of concrete prospects for support for carers and their own ageing. Conclusio: In our times, the social organisation of care is increasingly incompatible with human dignity and compatible with the prevailing mode of production and financial capital, laying bare its contradictions and unsustainability.
The organisation of social care in the context of an ageing population: a theoretical and practical perspective
Keywords: Trabalho; Cuidado informal; Envelhecimento; Gênero; Proteção social; Work; Informal care; Ageing; Genre; Social protection; CIENCIAS DA SAUDE::SAUDE COLETIVA; 5. Igualdade de Gênero; 8. Trabalho Decente e Crescimento Econômico; 10. Redução das Desigualdades